Improving The Knowledge Of Primary School Children On Fourth Grade Stundents About Vegetables And Fruits And Attraction Of Puzzle Media In SDN Mekarjaya I - Wiena Arynda; Rosmida M Marbun (Politeknik Kesehatan Kemenkes Jakarta II, 2017)
In Indonesia, 93.5% of the population aged ≥10 years still consume less fruits and vegetables 5 servings per day for 7 days a week (RISKESDAS, 2013). The preliminary study conducted at SDN Mekarjaya I shows that the level of knowledge of school children about vegetables and fruits by 60% is still low and 93.3% of vegetable and fruit consumption is still lacking. In addition, SDN Mekarjaya I has never been used as a place of prior research. Therefore, it is necessary to conduct research on the knowledge of fruit vegetables in the fourth grade students of SDN Mekarjaya I. One of them is by doing counseling with the media of puzzle game. This research was conducted to know the increase of knowledge about vegetables and fruits before and after given counseling with puzzle game media in fourth grade students of SDN Mekarjaya I. This research was conducted by Pre-exsperiment method using